2018
DOI: 10.1021/acs.jafc.8b05194
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and DNA Damage Caused from Diazinon Exposure by Inhibiting the PI3K-AKT Pathway in Porcine Ovarian Granulosa Cells

Abstract: Organophosphorus insecticide diazinon (DZN) is diffusely used in agriculture, home gardening, and crop peats. Much work so far has focused on the link between DZN exposure and the occurrence of neurological diseases, while little is known on the reproductive toxicological assessment on DZN exposure. This research aimed to investigate the underlying mechanisms of toxic hazards for DZN exposure on cultured porcine ovarian granulosa cells. We analyzed the oxidative stress, energy metabolism, DNA damage, apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…In addition, the PI3K/AKT pathway participates in oocyte growth, primordial follicular development, and granulosa cell proliferation and apoptosis. In previous studies, cytotoxic drugs were found to lead to apoptosis of granulosa cells and increase the risk of developing POF by significantly inhibiting the PI3K/AKT signaling pathway [24]. However, whether PI3K/AKT signaling is involved in ESCs-sEVs treatment for POF remained to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PI3K/AKT pathway participates in oocyte growth, primordial follicular development, and granulosa cell proliferation and apoptosis. In previous studies, cytotoxic drugs were found to lead to apoptosis of granulosa cells and increase the risk of developing POF by significantly inhibiting the PI3K/AKT signaling pathway [24]. However, whether PI3K/AKT signaling is involved in ESCs-sEVs treatment for POF remained to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes were processed by using the oxidation-sensitive fluorescent probe at 37 °C for 30 min according to the Reactive Oxygen Species Assay Kit (Beyotime Institute of Biotechnology, Shanghai, China). To detect the fluorescent intensity of ROS, the confocal system was used with the same scanning settings [27].…”
Section: Methodsmentioning
confidence: 99%
“…5,35,36 In other tissues, Wang and colleagues showed that cytotoxicity and DNA damage were caused by diazinon exposure through inhibiting the PI3K-AKT pathway in porcine ovarian granulosa cells. 37 Therefore, it seems that in the brain tissue, diazinon with increasing oxidative stress affected PI3K, CKD1, ERK and TRKB and reduction in these factors increases susceptibility of the brain to degenerative disease. Using herbal supplements can reduce the destructive effects of the ROS.…”
Section: Discussionmentioning
confidence: 99%